Bootstrap Technique For Examining The Properties Of The Maximum Likelihood Estimator Of The Spatial Unilateral Autoregressive Model. - Awang, Norhashidah; Rahayu, Latifah (2009)
Many methods and procedures have been developed and proposed to overcome the estimation problem in spatial modelling, for example, by defining classes of models called separable models and the unilateral models.